KORELASI ATRIBUT MUSLIM TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN DI UMKM KULINER KOTA MATARAM - Zaenul Wahyudi; Selamat Riadi (Nusantara Hasana Journal, 2025)
This study aims to analyze the strong and significant relationship between the Muslim attributes of culinary MSME merchants and consumer purchase decisions in Mataram City. The background of this study stems from the importance of the principle of halal (permissible) as a main pillar of Muslim consumer behavior, especially in Mataram, which focuses on the development of halal tourism. At the MSME level, halal certification is often conveyed thru informal visual and personal signals. The Muslim attributes that are the focus of this research are: the use of the hijab by female vendors, the presence of banners/writings with Muslim phrases (e.g., 'Halal', 'Muslim', or 'Bismillah'), and the absence of tattoos on male vendors. This correlational quantitative study used a sample of Al-Azhar University (UNIZAR) students, with data collected thru structured questionnaires and analyzed using Pearson Product Moment Correlation Analysis. The research results show a very strong and significant effect. The Significance Test (t-test) yielded a calculated t-value of 12.056 with a significance level of 0.000, which statistically proves that the Muslim attribute has a positive influence on purchasing decisions. The strength of this relationship is indicated by a Correlation Coefficient (R) of 0.917 and a Coefficient of Determination (R2) of 0.841 (or 84.1%), confirming that 84.1% of the variation in purchasing decisions is explained by Muslim Attributes. This finding supports the theory of Islamic Consumption Behavior, concluding that for religiously sensitive consumers in Mataram, Muslim attributes are a primary determinant of purchasing decisions. Therefore, culinary MSMEs are advised to prioritize Islamic ethics and visual communication to build trust and increase competitiveness.